The optimal proportion of state-owned shares in an industry chain - Kong, Xiao; Sun, Chaoqun; Liu, Jiali; Chen, Junlong (Technological and Economic Development of Economy, 2022)
This study focuses on the mixed-ownership reform of state-owned enterprises in an industry chain. By constructing an oligopoly model considering the proportion of state-owned shares and product differentiation, this study examines the impacts of the balance of state-owned shares and product differentiation in four scenarios, and analyzes the proportion of state-owned shares to maximize the social welfare of the industry chain. The results reveal a synergistic relationship between the balance of state-owned shares and product differentiation. The equilibrium results vary in different industry chain links and competition modes. The implementation of mixed ownership by upstream enterprises will help improve the overall efficiency of the industry chain. Complete nationalization may be optimal and an upstream monopoly can be realized under certain conditions.